Multiple intelligences, a methodology to improve verbal understanding. (2022)
The aim of this paper is to explore the relationship between multiple intelligences and verbal comprehension of students in 5th grade students of Basic Education. A sample of 34 subjects aged between 10 and 13 years (M= 11.33; DT= 0.32) was used. The level of multiple intelligences was analyzed through the inventory on Multiple Intelligences (Armstrong, 1999; adapted by Prieto and Ballester, 2003) and verbal comprehension index using the Wechsler Intelligence Scale for Children Revised; (WICSIV; Wechsler, 2005). The results show positive correlations and statistically significant between intrapersonal intelligence and naturalist intelligence and verbal comprehension. However, no positive correlations were found between speech understanding and other intelligence. Following is an intervention program designed to strengthen understanding through verbal methodology focused on intelligence multiple.